Impact of Tofu X Factory Liquid Waste Discharge on Gentung River Water Quality, Pangkep Regency: Dampak Buangan Limbah Cair Pabrik Tahu X Terhadap Kualitas Air Sungai Gentung, Kabupaten Pangkep - Nasrul, Nasrul; Amal Arfan; Nasiah Badwi; Ichsan Invanni Baharuddin; Dinil Qaiyimah (Universitas Hasanuddin, 2024)
This research aims to determine the impact of tofu factory liquid waste on the water quality of the Gentung River, Pangkep Regency. Quantitative descriptive analysis is used to analyze and process data presented narratively. The data was obtained from laboratory test results taken from five sampling points (one wastewater sample point as a pollutant, three river water sample points in the tofu factory area, and one river water sample as comparative data) which was then compared with the water quality standard requirements of the secondclass river. Survey data, observations, and documentation were also used to strengthen the laboratory analysis results of this research. The research results show that tofu factory liquid waste hurts river water quality in terms of the parameters Total Suspended Solids (TSS), Total Dissolved Solids (TDS), Dissolved Solids (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Organic Matter. The temperature, color, and pH parameters meet the established river water quality standards. So, it can be seen that the water from the Gentung River, Pangkep Regency, which is in the Tofu Factory Area, cannot be used as a source of clean water for thecommunity and agricultural land and similar uses because the water is polluted. This research can be used as a source of information for local stakeholders who are taking steps to address environmental problems.